Burden of Care Among Mothers Having Children with Congenital Heart Diseases - Sharma, Nita; Sharma, Pratima; Mishra, Tulashi Adhikari (Journal of Nepal Paediatric Society, 2020)
Introduction: Congenital Heart Disease (CHD) is a problem with structure and function of the heart that is present at birth. Children with CHD require special care, treatment and follow up for a number of common conditions which may be quite straining to the care givers. The objective of the study was to find out the burden of care among mothers having children with CHD. Methods: This descriptive cross-sectional study was carried out in a cardiac centre of Nepal. A total of 95 mothers having children with CHD attending outpatient department of our institute were selected as the sample for the study using non-probability purposive sampling technique. A semi structured interview questionnaire consisting of the Modified Caregiver Strain Index was used to assess the burden of care among mothers having children with CHD. Frequency and percent were used to describe the variables and chi- square test at 0.05 significance level was used to analyse associations. Results: Most (77.9%) of the mothers were regularly strained to find that their children’s health condition was deteriorating due to CHD. Nearly half (44.2%) of the mothers always had financial constrain while giving care to the child, nearly half (40%) of the mothers had done emotional adjustments to take care of their children with CHD, another two-fifths (28.4%) of the mothers sometimes had disturbed sleep and almost half (46.3%) of the mothers were always upset due to some behaviour of their child with CHD. Half (50.5%) of the mothers had high level of burden of care. Statistically significant association were found between age of the mother and level of burden of care (p value = 0.05). Similarly, the type of family (p value = 0.005), age of the children (p value = 0.000) and type of CHD (p value = 0.002) were significantly associated with the level of burden of care among the mothers. Conclusion: The study concluded that mothers tend to feel less burden of care as the child grows older, mothers having children with cyanotic heart disease tend to experience more burden of care. Mothers of less than thirty years of age and living in a joint family also experience more burden of care.